Pengaruh Kuat Arus Dan Waktu Kontak Pada Proses Elektrokoagulasi Menggunakan Sel Al-Al Dengan Ketebalan 1 MM Untuk Penyisihan Ammonia Dari Limbah Cair Proses Pengolahan Minyak Bumi - Muhammad Fauzi; Syarfi Daud; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Every oil and gas processing activity will not be separated from the problem of Ammonia provision, there are still many difficulties. One of the problems that is currently emerging is the problem of the wastewater treatment process. one of the efforts to reduce ammoniacontent in oil processing industry waste is by electrocoagulation process. The aim of the study was to determine the ability of the electrocoagulation method to decrease Ammonia levels and determine the effect of strong current changes and changes in time to decreaseAmmonia. The electrode used is aluminum. Variations in current strength used are 2, 3, 4, 5 Ampere and reaction times of 20, 40, 60 and 80 minutes. The experimental resultsshowed that the best electrical current for ammonia removal was 5 amperes. The best reaction time in the ammonia removal process in this study was 80 minutes of reactiontime. Highest ammonia removal obtained in this study was 79.7% (initial ammonia 52.3 mg / L to 10.6 mg / L).Keywords : electrocoagulation, aluminum, petroleum processing waste, ammonia.